PERPUSTAKAAN RAMAH DIFABEL: Studi Pemanfaatan Aplikasi E-Journal bagi Mahasiswa Difabel Netra - Asroni, Ahmad (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2024)
This article examines the utilization of e-journals as an academic information source for visually impaired students in the effort to create an inclusive and disability-friendly library. In the digital era, accessibility to scientific reading materials is a crucial factor in promoting educational equity for students with disabilities. This study employs a qualitative research approach with a case study at the Library of UIN Sunan Kalijaga Yogyakarta. Data was collected through in-depth interviews, observations, and documentation. The findings indicate that e-journals provide significant benefits for visually impaired students, particularly in supporting their academic activities through accessibility features such as screen readers. Many visually impaired students gain substantial advantages when accessing e-journals using screen reader programs. The integration of e-journals with screen reader technology facilitates students in acquiring knowledge and information from various references quickly, effectively, and efficiently. Due to the speed, effectiveness, and efficiency of screen reader technology, visually impaired students can access a wide range of e-journals as frequently and extensively as needed.